CLEANER PRODUCTION PRACTICES, ENVIRONMENTAL MANAGEMENT AND NATIONAL POLICY DEVELOPMENT IN MALAYSIA FOR ELECTROPLATING ENTERPRISES - Wangel, Arne; Mohamed, Maketab; P, Agamuthu (Malaysian Journal of Science, 2004)
Cleaner technologies (CT) have been introduced into the Malaysian Small and Medium Enterprises (SME)-sector primarily by foreign donor supported project interventions. The establishment of the Environmental and Energy Technology Centre at SIRIM was funded by a grant from the Danish Co-operation for Environment and Development (DANCED), Ministry of Environment and Energy. Small and medium-scale enterprises (SMEs) were targeted within three sectors: Textile, food and electroplating industries. The paper illustrates the change in process &om the perspective of electroplating SMEs by reviewing the cleaner production options chosen, presenting figures on the results achieved, and discussing the experiences gained. Reviewing the approach and results of the Centre, as well as the status of cleaner production (CP) in Malaysia, the paper outlines the challenges for national policy making, when moving from promotion by project intervention towards sustainable practices in the SME sector at large. The paper draws upon data collection conducted by the research project ’A Study on Promotion and Implementation of Cleaner Production Practices in Malaysian Industry - Development of a National Program and Action Plan for Promotion of Cleaner Production’.